Global city blues - Solomon, Daniel (Island Press, 2003)
This is a book about the making of cities and the buildings that compose them. It is about the conditions under which an architect engaged in those activities now works, how those conditions evolved and why they are changing. It is about the qualities of life that are threatened by the ways cities are built at the beginning of the 21st century and intelligent response to those threats. It is about why the city planning ideas and the cultural cuisinart that came in the box with modern architecture are a lingering menace.